Synthesis of star shaped Ba1-xSrTiO3 (BST) powders - Khollam, Y. B.; Potdar, H. S.; Deshpande, S. B.; Gaikwad, A. B. (Materials Chemistry and Physics, 2006)
Uniform star shaped strontium substituted barium titanyl oxalate Ba1-xSrxTiO(C2O4)(2) (BSTO)/strontium substituted barium titanate, Ba1-xSrxTiO3 (BST) powders were prepared via a simple chemical co-precipitation route with x = 0.15, 0.20, and 0.25. The process involved an addition of 0.1 M solution of titanium tetrabutoxide (BTM) in isopropanol (IPA) to 0.1 M oxalic acid in IPA containing 0.2 M of H2O to produce titanyl oxalate precipitate which was further reacted with 0.1 M solution of ammonium oxalate to obtain 0.1 M clear homogeneous solution of ammonium titanyl oxalate (ATO) with pH 4.25 containing titanium in the form of soluble anionic oxalate species [TiO(C2O4)(2)(2-)]. Stoichiometric quantities of barium hydroxide and strontium nitrate were dissolved in distilled water and its pH was adjusted nearly equal to that of ATO (similar to 4.15) by drop wise addition of dilute HNO3 solution 1:10 (v/v). The addition of this mixed cation precursor solution to ATO solution resulted in precipitation of strontium substituted barium titanyl oxalate (BSTO) having star shaped morphology. The calcination of BSTO precursors at 730 degrees C for 4 h in air produced cubic BST powders (a(o) similar to 4.001, 3.996 and 3.991 angstrom for x = 0. 15, 0.20, 0.25, respectively) having star shaped morphology. SEM, XRD and IFTIR techniques were used to characterize the BSTO/BST powders. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; capping agent; Co-precipitation; Morphology

Enhanced shape anisotropy and magneto-optical birefringence by high energy ball milling in NixFe1-xFe2O4 ferrofluids - Nair, Swapna S.; Xavier, Francis; Joy, Pattayil Alias; Kulkarni, S. D.; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2008)
Ferrofluids belonging to the series NixFe1-xFe2O4 were synthesised by two different procedures-one by standard co-precipitation techniques, the other by co-precipitation for synthesis of particles and dispersion aided by high-energy ball milling with a view to understand the effect of strain and size anisotropy on the magneto-optical properties of ferrofluids. The birefringence measurements were carried out using a standard ellipsometer. The birefringence signal obtained for chemically synthesised samples was satisfactorily fitted to the standard second Langevin function. The ball-milled ferrofluids showed a deviation and their birefringence was enhanced by an order. This large enhancement in the birefringence value cannot be attributed to the increase in grain size of the samples, considering that the grain sizes of sample synthesised by both modes are comparable; instead, it can be attributed to the lattice strain-induced shape anisotropy(oblation) arising from the high-energy ball-milling process. Thus magnetic-optical (MO) signals can be tuned by ball-milling process, which can find potential applications. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: birefringence; Co-precipitation; ferrofluid; HEBM

Copper-based catalysts for water gas shift reaction: influence of support on their catalytic activity - Pradhan, S.; Reddy, A. Satyanarayana; Devi, R. N.; Chilukuri, Satyanarayana V. (Catalysis Today, 2009)
Three copper containing catalysts supported on ceria and mixed oxides of ceria with zirconia and titania were prepared by co-precipitation method and their catalytic activity was tested for water gas shift (WGS) reaction. High surface area (>100m(2)/g) mixed oxides were obtained following the present method of preparation. The catalysts were characterized by XRD, H(2)-temperature programmed reduction (TPR), UV-vis and XPS. Catalytic activity was evaluated for water gas shift reaction in the 200-400 degrees C temperature range, The gas hourly space velocity was varied from 5000 to 25,000h(-1) for better evaluation and comparison of their performance. The effect of CO(2) in the feed gas mixture on the WGS activity of these catalysts was also studied. Among the three catalysts studied, CuO-CeO(2)-ZrO(2) mixed oxide shows better activity, implying the influence of support. Characterization of the catalysts after WGS reaction was also carried out in order to investigate structure-property correlation. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: ceria; Ceria-titania; Ceria-zirconia; Co-precipitation; Copper; Water gas shift

Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR

Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide

Magnetic and luminescent multifunctional nanohybrid: Fe3O4@CaF2:Tb3+: a facile synthesis and characterization - Vats, Monika; Kumar, Rakesh; Sharma, Jyotsna; Luwang, Meitram Niraj (Indian Journal of Pure & Applied Physics, 2020)
In the present study, bi-functional hybrid nanomaterial has been synthesized and characterized via facile method and characterized. The synthesized nanomaterial shows both magnetic and luminescent properties which are confirmed by VSM (vibrating sample magnetometer), UV-Vis spectra and the photoluminescence emission spectra. For the magnetic phase, i.e., nanocrystalline magnetite, Fe3O4 is used as the core which is then functionalized using polyethylene glycol (PEG) and for the luminescent phase, polyethylenimine (PEI) functionalized CaF2 doped with Tb3+ is used as the emitter. Wherein, both PEG and PEI serve the dual purpose of functionalization as well as stabilization by steric repulsion. The structure and morphology of the synthesized bifunctional hybrid nanomaterial are studied with the help of scanning electron microscopy (SEM) and X-ray powder diffraction.
Keywords: Biocompatible; CaF2; Co-precipitation; Fe3O4; Luminescent nanoparticle; Magnetic nanoparticles; Nanohybrid; Tb3+ doping